2021
DOI: 10.1101/2021.04.19.440533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene editing in Farm Animals: A Step Change for Eliminating Epidemics on our Doorstep?

Abstract: Recent breakthroughs in gene-editing technologies that can render individuals fully resistant to infections may offer unprecedented opportunities for controlling future epidemics. Yet, their potential for reducing disease spread are poorly understood as the necessary theoretical framework for estimating epidemiological effects arising from gene editing applications is currently lacking. Here, we develop semi-stochastic modelling approaches to investigate how the adoption of gene editing may affect infectious d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…When disease resistance can be linked to a single gene, resistant animals can be generated via genome editing and be incorporated into breeding programs [121]. For example, for PRRS-resistant pigs, the control of PRRSV is limited due to the moderate efficacy of inactivated vaccines and the safety risk of modified live virus vaccines [122].…”
Section: Eliminating Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…When disease resistance can be linked to a single gene, resistant animals can be generated via genome editing and be incorporated into breeding programs [121]. For example, for PRRS-resistant pigs, the control of PRRSV is limited due to the moderate efficacy of inactivated vaccines and the safety risk of modified live virus vaccines [122].…”
Section: Eliminating Susceptibilitymentioning
confidence: 99%
“…The model showed that when all farms are exposed at an average reproductive rate of 1.5 of PRRSV and the vaccine is 70% effective, only 12% of the pigs would be need to be resistant to eliminate the disease. Hence, genome editing can potentially facilitate disease eradication [121].…”
Section: Eliminating Susceptibilitymentioning
confidence: 99%
“…The gene disruption should be accomplished without use of a transgene, using spontaneous mutation, chemically or physically induced mutation, or genome editing that leaves no trace. The target organism generated in this manner is not a genetically modified organism for legal and regulatory purposes in many countries (Petersen et al, 2022). Third, the survival-permissive factor must be modified into a form that can be used when supplied extracellularly, and the modified factor must not exist in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Genome/gene-editing (GE) techniques include zinc finger nuclease (ZFN)-, transcription activator-like effector nuclease (TALEN)-, and clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated (Cas) endoribonuclease 9 (Cas9)-based methods. The CRISPR/Cas9 method has become the dominant approach since it is characterized by a low technological barrier and high efficiency; its application in pigs has been recently reviewed [ 11 , 12 ], and its use to improve resilience/disease resistance with the goal of epidemic elimination is of particular interest [ 13 ]. In pig production, GE has been recognized as a precise NBT with promising outcomes in improving sustainable traits; although this has already been documented, the predicted valorization and commercialization of NBT for public use remain uncertain considering related legislation.…”
Section: Introductionmentioning
confidence: 99%